Filamentous influenza viruses - Dadonaite, B; Vijayakrishnan, S; Fodor, E; Bhella, D; Hutchinson, E (Microbiology Society, 2016)
Clinical isolates of influenza virus produce pleomorphic virus particles, including extremely long filamentous virions. In contrast, strains of influenza that have adapted to laboratory growth typically produce only spherical virions. As a result, the filamentous phenotype has been overlooked in most influenza virus research. Recent advances in imaging and improved animal models have highlighted the distinct structure and functional relevance of filamentous virions. In this review we summarise what is currently known about these strikingly elongated virus particles and discuss their possible roles in clinical infections.